Peace psychology in Asia - Montiel, Cristina Jayme (Springer, 2009)
In recent years, peace psychology has grown from a utopian idea to a means of transforming societies worldwide. Yet at the same time peacebuilding enjoys global appeal, the diversity of nations and regions demands interventions reflecting local cultures and realities. Peace Psychology in Asia shows this process in action, emphasizing concepts and methods diverging from those common to the US and Europe.